An enhancing effect attributed to a nonsynonymous mutation in SOYBEAN SEED SIZE 1, a SPINDLY‐like gene, is exploited in soybean domestication and improvement. Issue 4 (21st September 2022) - Zhu, Weiwei; Yang, Ce; Yong, Bin; Wang, Yan; Li, Bingbing; Gu, Yongzhe; Wei, Siming; An, Zhenghong; Sun, Wenkai; Qiu, Lijuan; He, Chaoying
Summary: Soybean ( Glycine max ) was domesticated from its wild relative Glycine soja . One‐hundred‐seed weight is one of the most important domesticated traits determining soybean yield; however, its underlying genetic basis remains elusive. We characterized a soybean seed size 1 ( sss1 ) mutant featuring large seeds compared to its wild‐type background. Positional cloning revealed that the candidate gene GmSSS1 encoded a SPINDLY homolog and was co‐located in a well‐identified quantitative trait locus (QTL)‐rich region on chromosome 19. Knocking out GmSSS1 resulted in small seeds, while overexpressing GmSSS1/Gmsss1 induced large seeds. Modulating GmSSS1 / Gmsss1 in transgenic plants can positively influence cell expansion and cell division. Relative to GmSSS1, one mutation leading to an E to Q substitution at the 182 nd residue in Gmsss1 conferred an enhancing effect on seed weight. GmSSS1 underwent diversification in wild‐type and cultivated soybean, and the alleles encoding the Gmsss1‐type substitution of 182 nd ‐Q, which originated along the central and downstream parts of the Yellow River, were selected and expanded during soybean domestication and improvement. We cloned the causative gene for the sss1 mutant, which is linked with a seed weight QTL, identified an elite allele of this gene for increasing seed weight, and provided new insights into soybean domestication and breeding.